Analisis Karakter Jalan Jalan Kombes H. Umar Kota Pagar Alam - Dyan Pratnamas; Muhamad Alfian (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
As it is known that the road characteristics on a road are determined by road capacity, traffic volume and average speed. Road capacity is determined by the width of the road, side barriers which are influenced by activities and land use activities on the left and right of the road, besides being influenced also by other factors such as city size distribution factors, road shoulder construction. land use in determining road capacity. As it is known that MKJI (Indonesian Road Capacity Manual) has a procedure for calculating road capacity but traffic volume conditions that are often far above road capacity raise a question mark for the evaluation of the road capacity requirements. In this study the actual road capacity calculation is based on the approach of traffic volume and actual average speed which then the results of these calculations are compared with the results of MKJI calculations. Survey of traffic volume and speed at the research location.